ISSUES AND CHALLENGES OF INDIAN POLITICAL ADMINISTRATION – A STUDY (International Journal of Food and Nutritional Sciences, 2023)
“This article highlights the status of women in different General Elections. It focuses on the under representation of women in Indian Politics. It is grounded along the election commission’s report on electoral participation and representation of women from 1957 to the recently held general elections in 2014. It offers a detailed image of women’s political participation and representation from being women electorate to voters, from women as candidates to women as representatives in Lok Sabha. It indicates, due to various political and non-political reasons women go on to face democratic deficit in government. The substantial representation of women is missing in proportion to their population. Despite an increase in voting percentage in the recently held assembly and general elections still women represent less as candidates and fewer as women legislators”